STUDY OF MARINE ECOTOURISM POTENTIAL IN BERHALA ISLAND LINGGA REGENCY RIAU ARCHIPELAGO PROVINCE - Rahmad Febriyandi; Joko Samiaji; Mubarak ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The study was conducted in May-June 2015 in Berhala Island and its surrounding waters. The aim of this study was to know the marine ecotourism potential in Berhala Island as marine ecotourism destination in the future. The method used in this study was a survey method. The data observed consist of exploration results and inventory attractions, respondents of tourist representation and in situ measurement of water quality parameters. Berhala Island had huge potential of marine ecotourism and has a tremendous opportunity to be developed as a marine ecotourism region. It was shown on the suitability of marine ecotourism development, both assessed based on the criteria of supporting tour, SWOT analysis, calculation the value of WTA and WTP to the calculation of potential economic value . The potential economic value of marine tourism in Berhala Island is Rp. 52,159,000 (in the agenda of the annual holiday). This value was sufficient with still lack of facilities in the Berhala Island and potentially will grow if there are a implementation of the construction and development in Berhala Island region in the future.Key Word: Potential, Marine Ecotourism, Berhala Island